A Study of Self-Burial of a Radioactive Waste Container by Deep Rock Melting. (29th October 2013) - Chen, Wenzhen; Hao, Jianli; Chen, Zhiyun
Abstract : Aiming at the problem of radioactive waste disposal, the concept and mechanism of self-burial by deep rock melting are presented. The rationality and feasibility of self-burial by deep rock melting are analyzed by comparing with deep geological burial. The heat threshold during the process of contact melting around a spherical heat source is defined. The descent velocities and burial depths of spherical waste containers with varying radius are calculated. The calculated depth is much smaller than that obtained in the related literature. The scheme is compared with the deep geological burial that is currently carried out by the main nuclear countries. It is found that, at the end of melting, a radioactive waste container can reach deep strata that are isolated from groundwater.